Railway reform & charges for the use of infrastructure (ECMT : Distributed by OECD Publication Service, 2005)
Over the last few years, much progress has been made in developing rail charges to ensure non-discriminatory access to, and efficient use of national rail networks, but in Europe the international dimension is still missing, particularly in terms of the freight market. Integration of European markets should provide great opportunities for rail freight transport to grow. The purpose of this report is to set out how barriers to this growth - arising from differences in the way trains pay to use national networks - can be overcome. It recommends moving to a set of simple charges for freight that create similar incentives for the management and planning of train operations across national borders.--publisher summary.